The Effect Of Environmental, Social, And Governance (ESG) On Employee Engagement Mediated By Work Commitment (Case Study At Bank Mandiri KCP Jakarta Kyai Tapa) - Putu Eragrostis Brizantha; Easter Tobing (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) on Employee Engagement mediated by Work Commitment among Bank Mandiri employees at the Jakarta Kyai Tapa branch. A quantitative approach was used with a census method of 50 respondents and data were collected through a Likert Scale questionnaire. The analysis techniques used include multiple linear regression analysis and mediation tests. The results of the study indicate that ESG has a positive and significant effect on Work Commitment, ESG has a positive and significant effect on Employee Engagement, and Work Commitment has a positive and significant effect on Employee Engagement. However, Work Commitment does not significantly mediate the effect of ESG on Employee Engagement. This means that ESG directly increases Employee Engagement without the need for increased Work Commitment. The results of the research from the Determination Coefficient (R²) value show a figure > 0.05 in each variable which makes the variable's influence positive and significant. This finding reinforces the importance of implementing ESG principles in organizations to increase employee engagement. The recommendation of this research is that further researchers can expand the research variables by adding other factors such as job satisfaction and further research can be conducted in other divisions and sectors